Bilateral implantation of toric multifocal additive intraocular lenses in pseudophakic eyes - Rabsilber, Tanja Marina; Kretz, Florian Tobias Alwin; Holzer, Mike P.; Fitting, Anna; Sanchez Borquez, Maria Jose; Auffarth, Gerd U. (Journal of cataract and refractive surgery, 2012)
A 41-year-old patient presented with hyperopia, astigmatism, and presbyopia for refractive treatment 6 years following cataract surgery. A toric multifocal additive intraocular lens with a near addition of +3.5 diopters (D) for sulcus implantation was chosen and implanted uneventfully. Follow-up examinations were performed from the first day until 9 months after surgery. A predictable refractive correction was seen, with a residual error of +0.125 D (spherical equivalent) in the right eye and emmetropia in the left eye. Monocular uncorrected distance visual acuity (UDVA) and uncorrected near visual acuity (UNVA) (40 cm) improved to 0.1 logMAR. It could not be improved further with near-add spectacles. Binocular UDVA and UNVA were 0.0 logMAR and 0.1 logMAR (80 cm), respectively. Both additive IOLs remained centered and on axis during the follow-up period. Spectacle independence was achieved, as was high patient satisfaction. Financial Disclosure: The International Vision Correction Research Centre received research grants related to this publication from the following companies: Dr. Schmidt Intraocularlinsen GmbH, Rayner Intraocular Lenses, Ltd., and Carl Zeiss Meditec AG. No author has a financial or proprietary interest in any material or method mentioned.
Gesehen am 20.11.2018